MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL CERITA MATERI DALIL PYTHAGORAS MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING PADA SISWA KELAS VIII-4 SMP NEGERI 1 SEI BINGAI TAHUN PELAJARAN 2017-2018 - Lamsah Saragih (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
This research is a Class Action Research (PTK) that aims to remind the ability to solve the problem of Pythagoras Dalil material through problem solving learning model in grade VIII-4 students of SMP Negeri 1 Sei Bingai Year 2017-2018. The subjects in this study were grade VIII-4 students in the 2017-2018 school year totaling 36 students. Male and female students as many as 19 students and 17 students. This research was conducted as many as 2 cycles. Each cycle is held as many as 2 meetings. This research uses qualitative research method with research model from Kemmis and Taggart, where the research design consists of planning activities, implementation (action), observation (observe), and reflection (reflection). Research data sources are primary data (observation and documentation) and secondary data (Pustaka studies). Data collection techniques using observation techniques and documentation with data collection instruments are test instruments of essay questions and observation sheets of student and teacher activities. The results of the data analysis showed that through the use of problem solving learning models, the ability to solve the story of grade VIII-4 students of SMP Negeri 1 Sei Bingai has improved in each cycle. In the initial cycle, the students who received the "Excellent" category and the "Good" category were all 12 students (34%). Then in cycle I increased, students with the category "Excellent" and category "Good" were all 31 students (86%) up to cycle II, the students who received the "Excellent" category and the "Good" category were all 33 students (92%). Based on these acquisitions, it can be concluded that the use of problem solving learning models can improve the ability to solve student story problems in the subjects of mathematics material Dalil Pythagoras.